PENGARUH MUSIM TERHADAP FLUKTUASI KADAR FOSFAT DAN NITRAT DI LAUT BANDA - Edward, Edward; Tarigan, M. M. (UI Scholars Hub, 2003)
The Influence of Season to Nitrate and Phosphate Content Eutrophication in Banda Sea. Observation on phosphate and nitrate nutrient content were carried out in May, August, November, 1996 and February 1997 in Banda Sea. The results showed the averages content of phosphate and nitrate in August is higher compared to May, November and February. Phosphate content in August 1.492 mg.at/l, while in May, November and February are 1.025 mg.at/l, 0.878 mg.at/l and 0.766 mg.at/l. Nitrate content in August is 1.932 mg.at/l, while in May, November and February are 0.975 mg.at/l, 0.804 mg.at/l and 0.670 mg.at/l respectively. This result fixed with statistical Analysis (Randomized Block Anova) (Fh > F t 1%). This condition is caused by upwelling process in Banda Sea at that time.